Effects of diabetes mellitus and cervical changes on scar healing after cesarean section - Doğru Şükran; Ezveci Huriye; Akkuş Fatih; Yaman Fikriye Karanfil; Alp Elifsena Canan; Gezginç Kazim (Journal of Ultrasonography)
This study aimed to evaluate the effects of diabetes mellitus and cervical dilatation on cesarean section scar healing.